Despotic bodies and transgressive bodies : Spanish culture from Francisco Franco to Jesús Franco - Pavlovic, Tatjana (SUNY series in Latin American and Iberian thought and culture., 2003)
"Focusing on Spanish culture and society in the second half of the twentieth century, Despotic Bodies and Transgressive Bodies traverses a variety of disciplines: literature, film studies, cultural studies, feminist theory, and history, to examine crucial moments of cultural transition. Beginning with an analysis of the period of autarky - Spain's economic, cultural, and ideological isolation under Francisco Franco's regime - Pavlovic then explores the tumultuous passage to capitalism in the late 1950s and 1960s. She follows this by revisiting the complex political situation following Franco's death and points out the difficulties in Spain's transition from dictatorship to democracy. Combining a strong theoretical background with a detailed study of marginalized texts (La fiel infanteria), genres (the Spanish comedy known as the comedia sexy celtiberica), and film directors (Jesus Franco), Pavlovic reveals the construction of Spanish national identity through years of cultural tensions."--Jacket